ANALYSIS OF LANGUAGE ERRORS IN ONE OKEZONE MEDIA JOURNALISTIC PRODUCT - Anjani Lintang Pertiwi; Aulia Afifah; Vanessa Viviana Shodiq; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
This research is motivated by language errors due to a lack of understanding of the language used, and inappropriate or imperfect language teaching often occurs in the mass media. The method used in this research is a descriptive method because in this research it analyzes and examines a research data object according to the facts. The data collection technique is by reading and analyzing language errors from the text. The data collection instruments used were a feature text entitled